Survival and performance of seedlings planted for forest landscape restoration in the Oromia region of Ethiopia - Efrem Garedew; Abera Tesfaye; Menassie Gashaw; Teshome Tesema (Discover Agriculture)
Abstract Addressing environmental degradation in Ethiopia requires understanding the interconnectedness of deforestation with socio-economic dimensions such as land use rights, community engagement, and governance. This study evaluated seedling survival rates in Oromia during the First Growth and Transformation Plan (2011–2015) and found significant differences based on district (p = 0.0001), agroclimatic zone (p = 0.0013), species (p = 0.0003), and plantation land use rights (p = 0.0036). Higher rainfall was associated with better survival. Although this study provides an initial assessment of survival, its findings underscore the importance of seedling quality, site-species matching, planting methods, community participation, and government support for successful reforestation. These insights are vital for informing and improving Ethiopia's forest restoration policies and practices towards sustainable forest management, with recommendations focusing on developing species-site suitability guidelines, investing in research on the performance and ecological benefits of native species and strengthening community engagement. Further research is needed to evaluate the long-term ecological impacts of these efforts.